Urbanization and Renewable and Non-renewable Energy Consumption in OECD Countries: An Empirical Analysis - Salim, Ruhul; Shafiei, S. (Elsevier BV North-Holland, 2014)
This article aims to analyse the impact of urbanization on renewable and non-renewable energy consumption in OECD countries by using the STIRPAT model and data for the period of 1980 to 2011. Demographic factors including total population, urbanization and population density are found to be significant factors, particularly with respect to non-renewable energy consumption. The results also reveal that while total population and urbanization positively influence non-renewable energy consumption, population density has a negative impact on non-renewable energy consumption. From the demographic factors only total population has a significant impact on renewable energy consumption. Granger causality results indicate that there is unidirectional causality from non-renewable energy use to population density in the short run. However, no causal linkage is found between urbanization and non-renewable energy use. Likewise, no causal direction is seen between renewable energy use and any of the demographic factors.